Effect of high repetition rate on dimension and morphology of micro-hole drilled in metals by picosecond ultra-short pulse laser. (January 2020) - Zhao, Wanqin; Shen, Xiaowei; Liu, Haodong; Wang, Lingzhi; Jiang, Haitao
Highlights: Effect of repetition rate on micro-hole drilling by ultrafast laser is studied. Largest micro-shallow hole dimension is gotten at the critical repetition rate. High efficiency is gained for high repetition rate for micro-deep hole drilling. Effect of repetition rate on micro-hole morphology is presented firstly. Abstract: High repetition rate can produce high laser ablation efficiency. However, there is the issue of shortened pulses interval in the case of high repetition rate. Moreover, both the ejecting time of the ablated materials and the cooling time of the substrate material have been decreased, due to the high repetition rate. These all make some significant influences on micro-hole drilling using ultra-short pulse laser. In this paper, the effect of the repetition rate, on the dimension and morphology of micro- shallow and deep holes, has been systematically studied in metals ablated by picosecond ultra-short pulse laser. The relationship between the repetition rate and micro-hole dimensions, such as diameter and depth, is described. Most importantly, the effect of the repetition rate on micro-hole surface and side-wall morphology is presented for the first time. The possible influencing mechanisms are discussed.